An Analysis of Derivational Suffixes Found in CNN News: Entertainment Edition: - Dewa Ayu Giri Ulan; Ni Putu Cahyani Putri Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This research explores how derivational suffixes alter the meaning and grammatical category of words. The study analyzed derivational suffixes found in CNN News: Entertainment Edition, focusing on their types and functions. A descriptive qualitative method was employed, which involved reading the articles multiple times, selecting words with suffixes, and applying note-taking techniques to organize the data. Plag's (2002) theory was used to classify the derivational suffixes identified. CNN News was selected due to its up-to-date content and its status as a globally popular media outlet, widely read by diverse audiences. The analysis revealed a total of 233 derivational suffixes, categorized into four types: 4 instances of verb suffixes, 88 instances of adverb suffixes, 79 instances of nominal suffixes, and 62 instances of adjective suffixes. The results showed that adverb suffixes were the most prevalent in CNN News: Entertainment Edition. This finding suggested that adverbial modification played a significant role in the language of entertainment news. The study underscored the importance of understanding suffixes in analyzing contemporary media language.